INFLUENCE OF TAXPAYER WAGE INCOME, SOCIALIZATION AND INFORMATION QUALITY OF TRIPLE UNTUNG PROGRAM (MASSA PANDEMIC COVID-19) ON COMPLIANCE OF MOTOR VEHICLE TAXPAYERS IN SUBANG REGENCY (Case Study on Motor Vehicle Taxpayers in Subang Regency) - Evi Susilawati; Trisandi Eka Putri; Asep Kurniawan (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
This research aims to find out the influence of taxpayer wage income, socialization of triple profit program, quality of triple profit program information on Subang Regency taxpayers. The research method used in this study is a quantitative method with the number of respondents 200 taxpayers who have registered with the SAMSAT subang regency office. The data processing in this study used SPSS techniques. The results of this study showed that variable taxpayer wage income had no effect on the compliance of motor vehicle taxpayers, the socialization of th e triple profit program had a positive and significant effect on the compliance of motor vehicle taxpayers, and the quality of triple profit program information had a positive and significant effect on the compliance of motor vehicle taxpayers.